Rational inhibitor design, synthesis and evaluation as steps towards the discovery of new anti-tuberculosis drugs - Macnab, Elinor (2025)
Of all the infectious diseases that have ever plagued humankind (and animal-kind), tuberculosis (TB) remains one of the deadliest, having claimed some 1.3 million human lives in 2022 alone, to say nothing of its impact on the other species with which our lives are intertwined. Being a bacterial infection, TB is treatable with appropriate antibiotics, but the few drugs capable of killing or suppressing the growth of the remarkably hardy bacteria that cause the disease (primarily Mycobacterium tuberculosis in humans, and M. bovis in other species, most notably cattle) are rapidly losing their overall efficacy as antibiotic resistance rises in prevalence. The long and onerous treatment regimens required even in drug-sensitive cases – six months of up to four drugs, increasing to nine months if relatively moderate drug resistance has been confirmed, and even to twenty in extreme cases – and the potentially unbearable adverse effects of some of the therapies involved tend to lead to suboptimal patient compliance, hastening this already inevitable process, which has created an urgent, unmet need for novel anti-TB drugs. Starting from a recently reported, rationally designed inhibitor of InhA, an enoyl-acyl reductase involved in the synthesis of mycolic acids – crucial components of the mycobacterial cell wall – and a clinically validated target (the ultimate target of the first-line therapy isoniazid), a small library of seven compounds differing from each other at only one point (45 and 55-60) has been synthesised with the intention of generating a structure-activity relationship. Following computer simulations of their interactions with InhA and their pharmacokinetic and toxicological properties, their activity against M. smegmatis, a close relative of M. tuberculosis and M. bovis, has been assessed by multiple methods, and all seven appear to suppress bacterial growth to a similar and inconsistent degree, perhaps temporarily. Regrettably, they are also only sparingly soluble in water and have a tendency to form aggregates that rob them of their efficacy and interfere with some methods of evaluating biological activity. Nevertheless, there is crystallographic evidence that 58 may be capable of low-occupancy binding to its target, and some biochemical evidence of similarly weak binding between InhA and all but one of these compounds. Some refinement to the basic structure is needed to improve their solubility, but there is potential for these compounds to evolve into true drug leads. In parallel, the activity of the fungal natural product atrofuranic acid (AFA) and some of its derivatives (67-69) against M. tuberculosis and InhA has been probed by similar computational, microbiological and biochemical means, and seem rather more promising. AFA has been proved to bind to InhA, and both it and compound 69 have been shown to suppress mycobacterial growth at relatively low concentrations (5 µg mL-1), without the problematically low solubility of the fully synthetic compounds. Progress has also been made towards chemoenzymatic synthesis of other AFA derivatives, generated by feeding unnatural aromatic amino acids to the relevant fungi or supplying appropriate isolated enzymes with the corresponding pyruvic acids; this work is still ongoing.